Comparison of a 'freeze-all' strategy including GnRH agonist trigger versus a 'fresh transfer' strategy including hCG trigger in assisted reproductive technology (ART): a study protocol for a randomised controlled trial. Issue 7 (31st July 2017) - Stormlund, Sacha; Løssl, Kristine; Zedeler, Anne; Bogstad, Jeanette; Prætorius, Lisbeth; Nielsen, Henriette Svarre; Bungum, Mona; Skouby, Sven O.; Mikkelsen, Anne Lis; Andersen, Anders Nyboe; Bergh, Christina; Humaidan, Peter; et al.
Abstract : Introduction: Pregnancy rates after frozen embryo transfer (FET) have improved in recent years and are now approaching or even exceeding those obtained after fresh embryo transfer. This is partly due to improved laboratory techniques, but may also be caused by a more physiological hormonal and endometrial environment in FET cycles. Furthermore, the risk of ovarian hyperstimulation syndrome is practically eliminated in segmentation cycles followed by FET and the use of natural cycles in FETs may be beneficial for the postimplantational conditions of fetal development. However, a freeze-all strategy is not yet implemented as standard care due to limitations of large randomised trials showing a benefit of such a strategy. Thus, there is a need to test the concept against standard care in a randomised controlled design. This study aims to compare ongoing pregnancy and live birth rates between a freeze-all strategy with gonadotropin-releasing hormone (GnRH) agonist triggering versus human chorionic gonadotropin (hCG) trigger and fresh embryo transfer in a multicentre randomised controlled trial. Methods and analysis: Multicentre randomised, controlled, double-blinded trial of women undergoing assisted reproductive technology treatment including 424 normo-ovulatory women aged 18–39 years from Denmark and Sweden. Participants will be randomised (1:1) to either (1) GnRH agonist trigger and single vitrified-warmed blastocyst transfer in a subsequent hCG triggered natural menstrual cycle or (2) hCG trigger and single blastocyst transfer in the fresh (stimulated) cycle. The primary endpoint is to compare ongoing pregnancy rates per randomised patient in the two treatment groups after the first single blastocyst transfer. Ethics and dissemination: The study will be performed in accordance with the ethical principles in the Helsinki Declaration. The study is approved by the Scientific Ethical Committees in Denmark and Sweden. The results of the study will be publically disseminated. Trial registration number: NCT02746562; Pre-results.